2019
DOI: 10.1038/s41586-019-1373-2
|View full text |Cite
|
Sign up to set email alerts
|

A human liver cell atlas reveals heterogeneity and epithelial progenitors

Abstract: The human liver is an essential multifunctional organ, and liver diseases are rising with limited treatment options. However, the cellular composition of the liver remains poorly understood. Here, we performed single-cell RNA-sequencing of ~10,000 cells from normal liver tissue of 9 human donors to construct a human liver cell atlas. Our analysis revealed previously unknown sub-types among endothelial cells, Kupffer cells, and hepatocytes with transcriptome-wide zonation of some of these populations. We reveal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
922
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 881 publications
(1,025 citation statements)
references
References 44 publications
41
922
2
1
Order By: Relevance
“…By taking advantage of the knowledge on zonated hepatocyte transcriptomes, Halpern et al developed a paired‐cell sequencing approach to probe heterogeneity of liver endothelial cells and bioinformatically inferred their spatial information . Similar molecular signatures of LSEC zonation were observed in independent scRNA‐seq studies on NPCs isolated from healthy and NASH mouse liver and in human liver . Comparative analysis of LSEC transcriptomes obtained from healthy and NASH livers revealed profound defects in endothelial gene expression and vascular signaling that may contribute to disease pathogenesis .…”
Section: Liver Cell Heterogeneity and Zonation At Single‐cell Resolutionmentioning
confidence: 89%
See 2 more Smart Citations
“…By taking advantage of the knowledge on zonated hepatocyte transcriptomes, Halpern et al developed a paired‐cell sequencing approach to probe heterogeneity of liver endothelial cells and bioinformatically inferred their spatial information . Similar molecular signatures of LSEC zonation were observed in independent scRNA‐seq studies on NPCs isolated from healthy and NASH mouse liver and in human liver . Comparative analysis of LSEC transcriptomes obtained from healthy and NASH livers revealed profound defects in endothelial gene expression and vascular signaling that may contribute to disease pathogenesis .…”
Section: Liver Cell Heterogeneity and Zonation At Single‐cell Resolutionmentioning
confidence: 89%
“…RNA sequencing and proteomic analyses of these pooled hepatocytes revealed greater details of spatial gene expression in the liver at mRNA, micro RNA and protein levels. In a separate study, scRNA‐seq of human liver cells revealed remarkably conserved features of liver zonation between mouse and human …”
Section: Liver Cell Heterogeneity and Zonation At Single‐cell Resolutionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the first study, scRNA‐seq was performed in approximately 10,000 cells obtained from nine human donors to build a reference mRNA expression atlas for this organ, which is freely available for browsing and further exploration at http://human-liver-cell-atlas.ie-freiburg.mpg.de/. In depth analysis of this dataset reinforced again the notion that the liver is a highly heterogeneous organ, with identification of multiple subtypes of endothelial cells, Kupffer cells and hepatocytes, along with detection of a subpopulation of bile duct cells with liver progenitor features (Aizarani et al, ). These results expand on previously made observations by MacParland et al (), who identified multiple macrophage populations in the human liver.…”
Section: Liver Transcriptional Programsmentioning
confidence: 95%
“…For instance, the ability to unambiguously identify adult human liver stem cells or progenitor cells—their more restricted progeny—would profoundly affect the direction of translational research, yet the existence and characteristics of such cells remain hotly contested. In a recent study published in Nature , Aizarani and colleagues addressed this problem by interrogating the adult human liver environment on a single‐cell scale . In the second such study of its kind, Aizarani and colleagues used fresh and frozen cell preparations from 9 donors to map the gene expression of all major cell types in the human liver onto an interactive cell atlas.…”
mentioning
confidence: 99%